Designing with black architecture & interiors - Crafti, Stephen (Images Publishing, 2013)
Stephen Crafti has always been drawn to black houses, irrespective of the materials they are constructed in, be they zinc, timber or simply painted. Unlike most houses, which scream for attention, black houses sit quietly, accentuating the often-verdant landscape. There is also a sense of calm and tranquillity with a black home. Crafti doesn't live in a black house, but he recently upgraded a 1930's home. 'Everything I touched was changed to black, from the timber fences to the timber floorboards'. He even added black curtains and planted black bearded irises in his garden. Using black seemed to unify disparate elements in and around his home. While there are numerous black features in Crafti's home, his ideal scenario would be to live in a contemporary black house, with black furniture and black walls. And maybe even a garden filled with black plants. This book, showcasing black houses, is the starting point to this goal and will be organised according to the following themes: Black Exteriors; Living in Black; Details of Black; Kitchens & Dining in Black; and In Black And White.